TRADISI MUNGGAH MOLO DALAM PERSPEKTIF ANTROPOLAGI LINGUISTIK - Miftahul Ula (JURNAL PENELITIAN, 2010)
Munggah molo has become a tradition fulled by symbols and meanings. This anthropology-linguistics research reveals the symbols and meanings that have been grown in Pekalongan. The symbols in munggah molo tradition have an importan social function, particularly in composing social harmony of Pekalonganese. This harmony is not only valid for Javanese community of Pekalongan, but also for other communities like Chinese and Arabic ethnic. That is why it is very interesting